Dementia on Facebook: Requesting information and advice about dementia risk-prevention on social media. (October 2018) - Lawless, Michael; Augoustinos, Martha; LeCouteur, Amanda
Highlights: Facebook is an important platform for health communication and promotion. Health organisations can use Facebook to communicate with members of the public. Online health communication research can inform information and support provision. Abstract: Social media platforms like Facebook have the potential to make significant contributions to health communication and promotion, yet little is known about the social practices that routinely occur in such spaces. Health organisations can use social media to communicate about public health issues like the prevention of dementia for the purpose of improving population health outcomes. In this study, we examine posts on a conversation on a Facebook Page about dementia risk and prevention activity moderated by researchers affiliated with a prominent Australian dementia organisation. The analysis illustrates how posts in the conversation routinely functioned to make relevant and manage accountability and identity, and position users as responsible for risk-management. Understanding more about social norms of communicating about dementia risk-prevention online can provide insight into how posters experience and understand the issues of cognitive ageing and dementia, which may inform future tailored health communication strategies using social media. This is of significance given the increasing prevalence of dementia worldwide, and the growing importance of social media as sources of health information.